Occupational therapy and physiotherapy education and workforce in Anglophone sub-Saharan Africa countries - Augustine O. Agho; Emmanuel B. John (BMC, 2017)
Abstract Background Sub-Saharan Africa (SSA) countries are faced with the challenge of educating a critical mass of occupational therapists (OTs) and physiotherapists (PTs) to meet the growing demand for health and rehabilitation services. The World Federation of Occupational Therapy (WFOT) and World Confederation of Physical Therapy (WCPT) have argued for the need of graduate-level training for OTs and PTs for decades. However, very few studies have been conducted to determine the availability of OT and PT training programs and practitioners in SSA countries. Methods Initial data were collected and compiled from an extensive literature search conducted using MEDLINE and PubMed to examine the availability of OT and PT education and training programs in SSA countries. Additional data were collected, compiled, and collated from academic institutions, ministries of health, health professions associations, and licensing authorities in SSA countries. Secondary data were also collected from the websites of organizations such as the World Bank, World Health Organization (WHO), WFOT, and WCPT. Results This investigation revealed that there are limited number of OT and PT training programs and that these training programs in Anglophone SSA countries are offered at or below the bachelor's level. More than half of the countries do not have OT or PT training programs. The number of qualified OTs and PTs appears to be insufficient to meet the demand for rehabilitation services. Nigeria and South Africa are the only countries offering post-entry-level masters and doctoral-level training programs in physiotherapy and occupational therapy. Conclusions Higher learning institutions in SSA countries need to collaborate and partner with other regional and foreign universities to elevate the educational training and increase the supply of PTs and OTs in the region.